2014
DOI: 10.1016/j.neuron.2013.10.054
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to Background Light Enables Contrast Coding at Rod Bipolar Cell Synapses

Abstract: SUMMARY Rod photoreceptors contribute to vision over a ~6 log-unit range of light intensities. The wide dynamic range of rod vision is thought to depend upon light intensity-dependent switching between two parallel pathways linking rods to ganglion cells: a rod→rod bipolar (RB) cell pathway that operates at dim backgrounds and a rod→cone→cone bipolar cell pathway that operates at brighter backgrounds. We evaluated this conventional model of rod vision by recording rod-mediated light responses from ganglion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(107 citation statements)
references
References 51 publications
3
103
0
1
Order By: Relevance
“…RGC temporal tuning likely reflects the relative contribution of these different circuits. The RBC-AIIAC circuit is an example of a mixed rod-cone circuit and it would have slower temporal kinetics than cone circuits (15,27). Weakening of the RBC-AIIAC synapse could increase the relative contribution of faster circuits, leading to an acceleration of the RGC temporal tuning.…”
Section: Discussionmentioning
confidence: 99%
“…RGC temporal tuning likely reflects the relative contribution of these different circuits. The RBC-AIIAC circuit is an example of a mixed rod-cone circuit and it would have slower temporal kinetics than cone circuits (15,27). Weakening of the RBC-AIIAC synapse could increase the relative contribution of faster circuits, leading to an acceleration of the RGC temporal tuning.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the difference is in the extent of S-cone versus M-cone activation and their downstream bipolar cells. Although chromatic differences in targeting of different bipolar cell types has been explored in the adult mouse (Haverkamp et al, 2005;Breuninger et al, 2011;Wang et al, 2011;Euler et al, 2014), the specificity of wiring during development is unknown. Whether activity plays a role in the establishment of these synapses in the later maturing OFF pathway similar to what has been demonstrated for the ON pathway (Morgan et al, 2011;Dunn et al, 2013;Johnson and Kerschensteiner, 2014) remains to be determined.…”
Section: Late Development Of Off S-cone Pathwaymentioning
confidence: 99%
“…Responses across light conditions are mediated by different classes of photoreceptors: rod photoreceptors are active at low light levels, whereas S-cone and M-cone photoreceptors become active at bright light levels. In the mouse retina, rod-mediated signaling also contributes to visual processing in intermediate and bright light conditions (Ke et al, 2014; Szikra et al, 2014; Vlasits et al, 2014;Grimes et al, 2015;Tikidji-Hamburyan et al, 2015; Joesch and Meister, 2016), indicating that a complex set of interactions between rod and cone pathways influence the encoding features of the retina.Cones and rods feed into circuits that are initially distinct in the outer retina, but then converge onto the same cell types in the inner retina (Fig. 1A).…”
mentioning
confidence: 99%
“…primed vesicles for release at the presynaptic membrane (Heidelberger et al, 2005;Snellman et al, 2011). Recent studies have shown that the interplay of vesicle release and replenishment at the ribbon are important in encoding luminance and contrast by cones (Jackman et al, 2009;Babai et al, 2010) and rod BCs (RBCs; Oesch and Diamond, 2011;Ke et al, 2014).…”
Section: Introductionmentioning
confidence: 99%